Review Digital Learning Aid Systems for Enhancing Students’ Problem-Solving Skills in Physics Education: A Systematic Literature Review - Qurrota A'yun; Dwikoranto Dwikoranto; Rahmatta Thoriq Lintangesukmanjaya; Imam Sya'roni (Journal of Digitalization in Physics Education, 2026)
Objective: This study aims to examine how digital learning aid systems support the development of students’ problem solving skills in physics education. The study focuses on identifying how digital tools facilitate conceptual understanding, visualization of abstract physics concepts, inquiry based learning processes, and student engagement in solving physics problems. Method: This research uses a systematic literature review approach. Relevant studies were collected from international scientific databases and selected based on inclusion criteria related to digital learning systems, physics education, and problem solving skills. The selected articles were analyzed to identify learning mechanisms, instructional features, and patterns of digital technology use that support problem solving in physics learning environments. Results: The analysis shows that digital learning aid systems enhance problem solving through several instructional mechanisms. Interactive simulations, virtual experiments, visualization tools, and feedback systems help students understand physics concepts, explore relationships between variables, conduct inquiry based investigations, and evaluate solution strategies. These features support analytical thinking and structured problem solving processes. Novelty: This review highlights that digital learning aid systems function not only as instructional media but as integrated learning environments that simultaneously support conceptual understanding, visualization, inquiry processes, and student engagement to strengthen problem solving skills in physics education.